Climate Change and Migration in the MENA Region - Wodon, Quentin; Liverani, Andrea (World Bank, Washington, DC, 2015)
Climate change and climate-induced migration (Foresight, 2011) are major global concerns. This is true for the MENA region as well. Yet empirical data on how perceptions of climate change and weather shocks affect migration in the region are scarce. To what extent are perceived and actual weather shocks and changes in the environment driving temporary and permanent migration flows? Do remittances reach households living in climate poor areas, and if so, what is their impact on poverty and human development? These are some of the questions considered in a study by Wodon et al. (2014) based on various data sources including new household surveys for climate affected areas in Algeria, Egypt, Morocco, Syria, and Yemen (the five country sample in this note). In a short summary note as this one, it is important to be clear at the outset about what is measured and what is not. It is sometimes said that Climate is what we expect. Weather is what we get. Simply put, climate relates to the distribution of variables such as temperature and rainfall over a long period of time. This distribution is characterized by its moments, including the mean and the variance of key climatic variables. Climate change is then used to refer to the change in the distribution of rainfall and temperature. However, it is difficult to tell if the weather experienced at a point in time is due to climate change (the overall mean and variance of rainfall and temperature) or part of an existing distribution.